Doc Martin. Series 9 [videorecording (DVD)] - Clunes, Martin, 1961-; Catz, Caroline; McNeice, Ian; Marquez, John, 1970-; Ransom, Jessica, 1982- (Acorn, 2019)
All is not well for brilliant but boorish Dr. Martin Ellingham as the hit British dramedy returns. To Martin's utter disgust, his medical practice remains under official scrutiny because of his pre-existing blood phobia, and he is forced to attend refresher courses starting with phlebotomy. His wife, Louisa, and aunt Ruth urge him to take this risk to his career seriously, but events conspire against him.